Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Praktik Manajemen Laba - Ricardo, David Marciano; Faisal, Faisal (Diponegoro Journal of Accounting, 2015)
The purpose of this research is to determine the effect of corporate social responsibility disclosure , corporate characteristic such as profitibility, levergae, and size on the practice of earning management and how corporate characteristics moderating the relation of corporate social resposibility and earning management. The population in this study were all non-financial sector corporation listed in Indonesian Stock Exchange (BEI). The sample in this study was 151 of such corporations. Data were collected using observation. This reserearch found csr disclosure negatively affecting to earning management with discretionary accrual as the proxy. In addition, this research found profitability is a moderating variable between the relation of csr disclosure and earning management. Leverage and size cannot moderating the said relation.